Characterization and divergence analysis of different sunflower genotypes (Bangladesh Journal of Botany, 2025)
Twenty-one sunflower accessions were evaluated at the research field of Oilseed Research Centre (ORC), Bangladesh Agricultural Research Institute (BARI), Gazipur, to study the divergence within the genotypes. ORCGP-21 produced taller plants (160.4cm), thicker stems (2.2 cm), and maximum yield (525.2 g/plot). Maximum seed weight (80.0 g) was obtained from ORCGP-2 and ORCGP-13. ORCGP-15 produced the maximum oil percentage (40.3%). Significant and positive correlation of plot yield with days to 50% flowering (0.55**), plant height (0.80**), and stem diameter (0.56**) was observed. Days to 50% flowering had the highest direct positive contribution to on seed yield. Cluster analysis classified the 21 sunflower genotypes into two main groups. The maximum genetic divergence was observed between clusters I and cluster V. The phenotypic variability observed in this study suggests that these genotypes are potential germplasms for important traits and could be utilized in the development of superior sunflower cultivars.Bangladesh J. Bot. 54(4): 935-941, 2025 (December)